Technique Used in Translating Balinese Tradition Terms into French - Weddha Savitri, Putu (Lingual Journal of Language and Culture, 2017)
This paper aims to analyses the technique used in translating Balinese Tradition terms into French found in the Tourism Promotion Book of Bali Government Tourism Department. This book was published every year as one of the important device to promote Bali abroad especially to the French tourist. This paper is also to figure out whether there is loss and gain of information or skewing in conveying the meaning of the terms. The technique of translating from Harvey (2003) was applied to analyze the Cultural-bounded Terms and also the Theory from Nida (1974) was used as supporting theory. The findings showed that all translation technique are used in translating Balinese tradition and society terms, those are functional equivalence, formal equivalence, transcription or borrowing, and descriptive translation. Borrowing was mostly used by the translator in order to avoid skewing and to retain the SL meaning in the TL. The analysis also found that in the process of translating cultural terms, loss and gain, and skewing of information occurred   often and need more some revision to gain a better understanding about the terms. Keywords: Translation, equivalence, Balinese terms, French